2021
DOI: 10.3389/fcell.2021.653240
|View full text |Cite
|
Sign up to set email alerts
|

CARD-Associated Risk Score Features the Immune Landscape and Predicts the Responsiveness to Anti-PD-1 Therapy in IDH Wild-Type Gliomas

Abstract: BackgroundProteins containing the caspase recruitment domain (CARD) play critical roles in cell apoptosis and immunity. However, the impact of CARD genes in tumor immune cell infiltration, responsiveness to checkpoint immunotherapy, and clinical outcomes of gliomas remains unclear. Here, we explore using CARD genes to depict the immune microenvironment and predict the responsiveness of gliomas to anti-PD-1 therapy.MethodsThe genome and transcriptome data of 231 patients with isocitrate dehydrogenase wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…During the inflammatory response, CARD16 acts as a decoy to disrupt RIP2 binding to caspase-1 via CARD-CARD interaction, leading to the blockade of caspase-1 activity and the stimulation of NF-κB [ 59 ]. Our prior study demonstrated that a 6-gene signature including CARD16 features the tumor immune microenvironment and predicts the prognosis of IDH wild-type gliomas [ 60 ]. Herein, we demonstrated that CARD16 participates in the stemness maintenance of GSCs and the inhibition of cAMP-induced differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…During the inflammatory response, CARD16 acts as a decoy to disrupt RIP2 binding to caspase-1 via CARD-CARD interaction, leading to the blockade of caspase-1 activity and the stimulation of NF-κB [ 59 ]. Our prior study demonstrated that a 6-gene signature including CARD16 features the tumor immune microenvironment and predicts the prognosis of IDH wild-type gliomas [ 60 ]. Herein, we demonstrated that CARD16 participates in the stemness maintenance of GSCs and the inhibition of cAMP-induced differentiation.…”
Section: Discussionmentioning
confidence: 99%